PENINGKATAN KOMPETENSI GURU SEKOLAH LUAR BIASA DALAM PEMBELAJARAN INOVATIF BERBASIS TIK - I.D.M.B.A Darmawan (Buletin Udayana Mengabdi, 2024)
Educational transformation can be carried out by utilizing information technology in all activities of implementing learning in schools. This paper is the complete service at SLB N 2 Denpasar, which aims to provide an understanding of ICT-based Innovative learning. The service is carried out through training methods that provide education staff and teachers with an understanding of the use of cloud computing technology and various e-assessment methods to increase teachers' understanding of the use of Classroom as a Learning Management System. The training, carried out for 3 days, could run well by applying the collaborative method. The questionnaire results increase the understanding of the use of ICT in learning, and the material provided can improve work. Keywords: education transformation, elearning, classroom, cloud computing, tik, slb